Childhood tuberculosis in a South-East Nigerian tertiary hospital: Treatment outcomes and determinants - Onubogu, Chinyere; Ugochukwu, Ebele; Anyabolu, Arthur; Ojukwu, Juliet (Libyan International Medical University Journal, 2019)
Background and Objectives: Tuberculosis (TB) is an important cause of childhood morbidity and mortality. Understanding the barriers to successful childhood TB treatment is vital to curbing the scourge of childhood TB. This study examined the outcomes and factors that influence the outcomes of childhood TB treatment in a South-East Nigerian tertiary hospital. Methods: A 10-year review of the medical records of under-15 year olds, who received anti-TB treatment at Nnamdi Azikiwe University Teaching Hospital, Nnewi, was carried out. Data were analyzed using SPSS version 20. Results: Majority of the 501 childhood TB cases were new (89.6%) and pulmonary (73.3%) TB cases. TB-HIV coinfection occurred in 42.5% of cases. The rate of successful treatment was 62.9%. About 57.5% completed treatment, 5.4% were cured, 7.0% were transferred out, 21.4% were lost to follow-up, 0.4% had treatment failure while 8.4% died. Majority (61.6%) of deaths or loss to follow-up occurred during the first 2 months of treatment. Factors significantly associated with treatment outcomes were ascertainment of HIV status (P = 0.049), disease site (P = 0.013), nutritional status (P = 0.039), Mantoux test result (P = 0.002), and period of treatment (P = 0.005). Conclusion: Findings indicate high rate of unsuccessful childhood TB treatment outcomes. Efforts should be intensified to ensure improved outcomes through proactive search for childhood TB cases, early diagnosis and treatment, as well as adherence to and completion of treatment. Special attention should be given to high-risk groups including those with unknown HIV status, extrapulmonary TB, and severe malnutrition. It is imperative to determine the HIV status of all childhood TB cases.
Keywords: Childhood tuberculosis; children; Nigeria; outcomes; treatment